INFLUENCE OF GIVING QUESTION AND GETTING ANSWER AS AN ACTIVE LEARNING MODEL CONTAINED SCIENCE LITERACY TO STUDENT LEARNING COMPETENCIES IN VIRUS MATERIAL SENIOR HIGH SCHOOL - Elsa Sastra; Relsas Yogica; Rahmawati D; Syamsurizal Syamsurizal (Universitas Negeri Padang, 2021)
Research on the problems that exist in Adabiah Padang Senior High School, student learning competencies are still low. The effort that can be done is to apply the active learning model giving questioan and getting answer type with literacy content of SMAN Adabiah Padang. The purpose of this study was to study learning through an active model of giving questioan and getting answer type with literacy at SMA Adabiah Padang. This type of research is experimental research with randomized posttest control group design. The population in this study were all students of class X IPA SMA Adabiah Padang registered in 2019/2020. Sampling was done using the Simple purposive sampling technique, which was chosen as the research sample was class X IPA.4 as the experimental class and X IPA.3 as the control class. The instrument used consisted of posttest questions for knowledge competencies, observation sheets for competencies and skills. The assessment hypothesis using the t-test, can prove the knowledge competency tcount 7,90>ttable 1.67, competency assessment value 84% with very good categories and competency skills value tcount 3.65>ttable 1.84. This is an accepted hypothesis. It was concluded that the cooperative model of giving questioan and getting answer type with literacy opposed the competence of knowledge, attitudes, and skills of class X IPA students of SMA Adabiah Padang.